Kristologi Dalam Injil Sinoptik - Daniel Tumbel (Jurnal Teologi dan Pelayanan Kerusso, 2016)
Confusion may occur in considering Jesus’ function in the Gospels without comprehending the different terminology used for Him. Without a clear understanding of such terms that are appled to Jesus, one will be left with a fragmentary perspective of the person of Jesus, which will result in misinterpreting God’s Word and miss His will for believers. The Gospels are the biographies that develop the life of Jesus Christ. They are the seed-bed from which Jesus’ twelve apostles and other followers derived most their theology and information about Him. Within the study Christology found in gospel genre, understanding the following five terms gives a complete picture of Jesus: Christ, Lord, Servant of Yahweh, the Son of Man, and the Son of God.